2021
DOI: 10.1001/jama.2021.7217
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Gestational Diabetes at First Live Birth by Race and Ethnicity in the US, 2011-2019

Abstract: OBJECTIVE To determine whether rates of gestational diabetes among individuals at first live birth changed from 2011 to 2019 and how these rates differ by race and ethnicity in the US.DESIGN, SETTING, AND PARTICIPANTS Serial cross-sectional analysis using National Center for Health Statistics data for 12 610 235 individuals aged 15 to 44 years with singleton first live births from 2011 to 2019 in the US.EXPOSURES Gestational diabetes data stratified by the following race and ethnicity groups: Hispanic/Latina (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
158
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 189 publications
(168 citation statements)
references
References 40 publications
9
158
0
1
Order By: Relevance
“…Our findings are also consistent with prior reports of heterogeneity in cardiovascular health and disease outcomes in Asian American subgroups, including in leading causes of death, 10 treatment patterns and outcomes for coronary artery disease, 11 and burden of cardiovascular risk factors among Asian Americans. 5,12 Our findings also align with data showing substantial burden of premature mortality from cardiovascular causes in Asian American subgroups. 13 Differences in burden of risk factors like hypertension, obesity, diabetes, and smoking likely contribute in part to the heterogeneity observed in cardiovascular and cerebrovascular mortality outcomes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings are also consistent with prior reports of heterogeneity in cardiovascular health and disease outcomes in Asian American subgroups, including in leading causes of death, 10 treatment patterns and outcomes for coronary artery disease, 11 and burden of cardiovascular risk factors among Asian Americans. 5,12 Our findings also align with data showing substantial burden of premature mortality from cardiovascular causes in Asian American subgroups. 13 Differences in burden of risk factors like hypertension, obesity, diabetes, and smoking likely contribute in part to the heterogeneity observed in cardiovascular and cerebrovascular mortality outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…One analysis of gestational diabetes surveillance in disaggregated Asian American subgroups from the National Center for Health Statistics between 2011 and 2019 revealed a range of gestational diabetes rates, from 54 per 1000 live births in Japanese women, to 129 per 1000 live births in Asian Indian women. 5 As cardiovascular risk factors are not uniformly distributed in Asian American subgroups, understanding cardiovascular and cerebrovascular disease mortality in disaggregated Asian American subgroups is necessary to understand health and disease in these populations.…”
mentioning
confidence: 99%
“…Racial disparities in health care access and health are well documented in the US. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 While expanding health insurance coverage reduces disparities, 9 , 10 , 11 , 12 , 13 , 14 , 15 substantial unexplained variation remains. Prior studies found that racial disparities persist among US children and adults with the same sources of health insurance 16 , 17 , 18 , 19 , 20 and those treated by the same health systems.…”
Section: Introductionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is diagnosed when glucose intolerance develops after 20 weeks of pregnancy in a woman who previously did not have diabetes [1]. According to a recent study, the incidence of GDM sharply increased by 30% in wom-en aged 15 to 44 years who had their first live birth between 2011 and 2019, and the highest rate of increase was noted among women of Asian descent [2]. GDM increases the risk of perinatal complications [1].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we hypothesized that diabetes management self-efficacy was crucial for pregnant women with GDM to successfully practice diabetes management, and that various psychological, emotional, and physical factors could influence that self-efficacy. However, the existing literature has been focused on the changing trends in the treatment of pregnant women with GDM [2,3], the influence of self-efficacy on improved treatment compliance in this population [4], and the level of improvement in self-management or blood sugar control after interventions [10]. To the authors' knowledge, no studies have yet investigated the influence of the factors introduced above on the level of diabetes management self-efficacy.…”
Section: Introductionmentioning
confidence: 99%